2015
DOI: 10.2341/15-038-c
|View full text |Cite
|
Sign up to set email alerts
|

Two-year Randomized, Controlled Clinical Trial of a Flowable and Conventional Composite in Class I Restorations

Abstract: The flowable and conventional composites used in this study have similar clinical efficacy after two years of service when placed as Class I occlusal restorations having isthmus widths less than one-half the intercuspal distance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 26 publications
2
24
0
7
Order By: Relevance
“…Consequently, an increased rate for marginal discoloration, marginal adaptation and secondary caries is expected. However, a clinical study reported that, after two years, a flowable composite showed the results that were similar to a conventional resin composite (26). In the present study, after 5 years, the flowable composites exhibited similar results.…”
Section: Raspravasupporting
confidence: 72%
See 1 more Smart Citation
“…Consequently, an increased rate for marginal discoloration, marginal adaptation and secondary caries is expected. However, a clinical study reported that, after two years, a flowable composite showed the results that were similar to a conventional resin composite (26). In the present study, after 5 years, the flowable composites exhibited similar results.…”
Section: Raspravasupporting
confidence: 72%
“…U skladu s tim, očekuju se češće rubne promjene boje, lošija rubna prilagodba i sekundarni karijes. No u jednom kliničkom istraživanju istaknuto je da je nakon dvije godine tekući kompozit imao slične rezultate kao konvencionalni (26). U ovom su istraživanju nakon pet godina tekući kompoziti pokazali slične rezultate.…”
Section: Raspravaunclassified
“…A study by Lawson et al reported similar clinical color match after 2 years of service between microfilled flowable and conventional composites. [13] In a 4-year clinical evaluation by Schirrmeister et al, Ceram•X demonstrated acceptable marginal discoloration. [14] Finally, Filtek Supreme XT and Gradia Direct posterior showed acceptable clinical performance and color stability after 5-year and 3-year clinical evaluations, respectively.…”
Section: Discoloration Of Different Esthetic Restorative Materials: Amentioning
confidence: 99%
“…For better flowability, previously‐used flowable‐type composites contained less filler, thus were mainly used in the lining of the cavity and the filling of the cavity free from occlusal pressure . Recently, nanotechnology, as well as filler surface preparation technology, have greatly improved the properties of flowable‐type composites, which has led to development of a new flowable‐type composite with good strength, abrasion resistance, and excellent anatomy‐forming properties, and expanded clinical application for the occlusal cavity …”
Section: Introductionmentioning
confidence: 99%
“…19,20 Recently, nanotechnology, as well as filler surface preparation technology, have greatly improved the properties of flowabletype composites, 12,21 which has led to development of a new flowable-type composite with good strength, abrasion resistance, and excellent anatomy-forming properties, and expanded clinical application for the occlusal cavity. [22][23][24] In the present study, a newly-developed, flowable-type nano-hybrid composite (MI FIL [MI group], G-aenial Universal Flo; GC, Tokyo, Japan) and Heliomolar (HM group) were clinically evaluated for 2 years to compare their performance in posterior cavity restoration cases. The hypothesis tested was that clinical properties of the flowable-type nano-hybrid composite restorations show no difference from those of the paste-type composite restorations.…”
Section: Introductionmentioning
confidence: 99%